An Introduction to the Economics of Immigration in OECD Countries - Anthony Edo; Lionel Ragot; Hillel Rapoport; Sulin Sardoschau; Andreas Steinmayr; Arthur Sweetman (Institute of Labor Economics (IZA), 2020)
The share of the foreign-born in OECD countries is increasing, and this article summarizes economics research on the effects of immigration in those nations. Four broad topics are addressed: labor market issues, fiscal questions, the political economy of immigration, and productivity/international trade. Extreme concerns about deleterious labour market and fiscal impacts following from new immigrants are not found to be warranted. However, it is also clear that government policies and practices regarding the selection and integration of new migrants affect labour market, fiscal and social/cultural outcomes. Policies that are well informed, well crafted, and well executed beneficially improve population welfare.
Keywords: F22; J15; J61; 330; immigration; labor market and fiscal effects of immigration; integration; diversity and productivity; trade and migration; political economy of immigration; refugees